Modulation of a Neural Network by Physiological Levels of Oxygen in Lobster Stomatogastric Ganglion - Massabuau, Jean-Charles (J Neurosci, 1996)
Although a large body of literature has been devoted to the role of O(2) in the CNS, how neural networks function during long-term exposures to low but physiological O(2) partial pressure (Po(2)) has never been studied. We addressed this issue in crustaceans, where arterial blood Po(2) is set in the 1–3 kPa range, a level that is similar to the most frequently measured tissue Po(2) in the vertebrate CNS. We demonstrate that over its physiological range, O(2) can reversibly modify the activity of the pyloric network in the lobster Homarus gammarus. This network is composed of 12 identified neurons that spontaneously generate a triphasic rhythmic motor output in vitro as well as in vivo. When Po(2) decreased from 20 to 1 kPa, the pyloric cycle period increased by 30–40%, and the neuronal pattern was modified. These effects were all dose- and state-dependent. Specifically, we found that the single lateral pyloric (LP) neuron was responsible for the O(2)-mediated changes. At low Po(2), the LP burst duration increased without change in its intraburst firing frequency. Because LP inhibits the pyloric pacemaker neurons, the increased LP burst duration delayed the onset of each rhythmic pacemaker burst, thereby reducing significantly the cycling frequency. When we deleted LP, the network was no longer O(2)-sensitive. In conclusion, we propose that (1) O(2) has specific neuromodulator-like actions in the CNS and that (2) the physiological role of this reduction of activity and energy expenditure could be a key adaptation for tolerating low but physiological Po(2) in sensitive neural networks.